Energy Production with Hybrid Systems: Case Study of MAKU-TBMYO, Turkey - İbrahim KIRBAŞ; Tolga KOCAKULAK (Mehmet Akif Ersoy Üniversitesi Fen Bilimleri Enstitüsü, 2021)
These days, when considered together with the energy production, sustainability, economy and environmental issues, all authorities are gathered around the renewable energy sources. Decreasing of the costs and increasing of the efficiencies, thanks to the developing technologies, has rapidly increased the tendency towards renewable energy sources, especially solar and wind. Hybrid systems are gaining currency in order to make maximum use of the advantages of these systems and to minimize their disadvantages. In this study, the installation of hybrid systems formed with solar panels and wind turbines is evaluated on the campus of Burdur Mehmet Akif Ersoy University, Vocational School of Technical Sciences. System designs are carried out on the Homer Pro simulation program. The input of monthly energy consumption values of the campus has been supplied. As a result of the installation of pure solar, pure wind and with different combinations of hybrid power plant designs with 60 kW, 80 kW and 100 kW power capacities, the amount of purchased and sold energy values from the grid are calculated. Considering the initial installation costs and maintenance costs of the solar, wind and hybrid power plants, the amortisation periods of the systems and the profit amounts at the end of 10 and 25 years have been calculated. The obtained results were evaluated by examination in detail. It is obtained that the energy received from the grid is the least in the case of a 100 kW hybrid system is installed with a 50 kW solar panel and a 50 kW wind turbine. In case of the system is installed with a solar panel, continuous increase in the amount of generated energy is observed.